Assessment of greenhouse gas emission from yard-long-bean cultivation by farmers in Pathum Thani province - Aroonsrimorakot, Sayam; Kasibut, Kantapat; Schulte, Benjamin (Interdisciplinary Research Review, 2018)
This research on greenhouse gas emission from yard-long-bean (Vigna unguiculata subsp. sesquipedalis (L.) Verdcourt) cultivation aims 1) to study the methods and activities of yard-long-bean cultivation in Nong-Suea district and 2) to calculate greenhouse gases (GHG) generated from all activities of yard-long- bean cultivation throughout its life cycle. Random sampling of 10 yard-long-bean farmers provided the basis for analysis that covers all activities of yard-long-bean cultivation, beginning from sourcing raw materials, planting, care, harvest, transportation, consumption and waste disposal. The study found that significant activities relating to GHG emissions were soil preparation, transplanting of sprouts, watering, fertilizer application, pole supports, bag covering, transportation, consumption and waste disposal. The average amount of greenhouse gases calculated from all activities was 743.06 kgCO2eq/ha. The result shows no significant differences in GHG emission between the farmers at the p-value of 0.469, while each activity generated greenhouse gases with significant differences at the p-value of 0.0009. Additionally, the 11-12 months periods of caring for the yard-long beans generated the highest emissions of GHG due to applications of fertilizers and chemicals as well as watering activities.